Electrochemical and Discharge Micro Machining: A Review - Goyal, PK; Singh, Kamal; Kumar Bhati, Sunil; Gehlot, Dilip (International Journal of Computer Sciences and Engineering, 2025)
Electrochemical micromachining is an advanced machining process that used for cutting complex shapes, 3-D profiles which is difficult for conventional machining. In the present work, reviews are conduct based on ECMM experimental investigations. The effect of ECMM process parameter on material removal rate (MRR), overcut (OC), kerf shape. Various optimization tools like Taguchi, Response surface methodology (RSM), as well as prediction tools like artificial neural network (ANN), finite element method (FEM), are implemented. ECMM offers several advantages including higher machining rate and better surface finish than another conventional machining process.